2011
DOI: 10.1097/jcp.0b013e3182239191
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mifepristone for the Treatment of Psychotic Depression

Abstract: Open-label studies and randomized clinical trials have suggested that mifepristone may be effective for the treatment of major depression with psychotic features (psychotic depression). A recent study reported a correlation between mifepristone plasma concentration and clinical response. The current study aimed to evaluate the safety and efficacy of mifepristone and, secondarily, to test whether response was significantly greater among patients with mifepristone plasma concentrations above an a priori hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 25 publications
0
48
0
Order By: Relevance
“…Similar normalizing effects of mifepristone treatment were observed with regard to neurogenesis in the dentate gyrus (Oomen et al, 2007). These cellular actions of the antiglucocorticoid possibly contribute to its beneficial effect in severe cases of psychotic depression, provided sufficiently high concentrations in plasma are achieved (DeBattista et al, 2006;Gallagher et al, 2008;Blasey et al, 2011). Whether mifepristone exerts its effects only via blockade of GRs is hard to judge, given the many adaptive actions that may occur, both peripherally and in the brain (Kling et al, 2009).…”
Section: Disease and Targets For Treatmentmentioning
confidence: 90%
“…Similar normalizing effects of mifepristone treatment were observed with regard to neurogenesis in the dentate gyrus (Oomen et al, 2007). These cellular actions of the antiglucocorticoid possibly contribute to its beneficial effect in severe cases of psychotic depression, provided sufficiently high concentrations in plasma are achieved (DeBattista et al, 2006;Gallagher et al, 2008;Blasey et al, 2011). Whether mifepristone exerts its effects only via blockade of GRs is hard to judge, given the many adaptive actions that may occur, both peripherally and in the brain (Kling et al, 2009).…”
Section: Disease and Targets For Treatmentmentioning
confidence: 90%
“…There have also been a number of studies conducted using mifepristone in (non-Cushing's) patients with pMDD. Positive findings in the initial open studies [Belanoff et al 2001[Belanoff et al , 2002Simpson et al 2005] and randomized controlled trials [DeBattista et al 2006; Flores et al 2006] have been followed by a larger negative trial [Blasey et al 2011], which used reduction in psychotic symptoms as the outcome measure. The authors argue that higher mifepristone doses may have led to a more robust response.…”
Section: The Hypothalamic-pituitary-adrenal Axis As a Target For The mentioning
confidence: 99%
“…133 A further trial has shown the importance of plasma levels of mifepristone, with a benefit seen in patients whose levels were above a cut-off point. 134 The group is conducting a further clinical trial of mifepristone in psychotic major depression using the higher (1,200 mg) dose. 135 Our group 136 reported selective improvements in spatial working memory performance, verbal fluency, and spatial recognition memory following treatment with mifepristone 600 mg/day in a 3-week, double-blind, crossover design in bipolar depression.…”
Section: Glucocorticoid Receptor Antagonistsmentioning
confidence: 99%